A comparative study of using static and ultrasonic material testing methods to determine the anisotropic material properties of wood. (15th January 2016) - Dackermann, Ulrike; Elsener, Roman; Li, Jianchun; Crews, Keith
Highlights: Comparative analysis of static and ultrasonic testing for wood. Determination of all twelve orthotropic material properties of two hardwood species. Recommendations on the execution of the static and ultrasonic tests for wood. Abstract: This paper presents a comparative study using static and ultrasonic testing for the determination of the full set of orthotropic material properties of wood. In the literature, material properties are typically only available in the longitudinal direction, and most international standards do not provide details on the testing of the other two secondary directions (radial and tangential). This work provides a comprehensive study and discussions on the determination of all twelve orthotropic material properties of two hardwood species using static testing and an alternative testing approach based on ultrasonic waves. Recommendations are given on the execution of the tests and the interpretation and calibration of the results.